2012
DOI: 10.21273/hortsci.47.5.614
|View full text |Cite
|
Sign up to set email alerts
|

Grafting for Root-knot Nematode Control and Yield Improvement in Organic Heirloom Tomato Production

Abstract: Organic heirloom tomatoes (Solanum lycopersicum L.) are difficult to grow in Florida as a result of root-knot nematodes (Meloidogyne spp.) (RKN) and hot, humid growing conditions. Although grafting with resistant rootstocks has been shown effective for RKN management in tomato production, little research has been conducted on grafted heirloom tomatoes under Florida conditions. In this 2-year study, two susceptible heirloom tomato scions, ‘Brandywine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 22 publications
(36 reference statements)
2
29
0
1
Order By: Relevance
“…Previous studies in our experimental system (53) and other grafted tomato systems (45,78,79) have indicated that tomatoes with effective rootstocks gain greater aboveground biomass and have higher overall photosynthetic activity, a result often attributed to the root system. A particular pairing of scion and rootstock may define the root nutrient and metabolite profile (42) through absorption and shoot feedbacks.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies in our experimental system (53) and other grafted tomato systems (45,78,79) have indicated that tomatoes with effective rootstocks gain greater aboveground biomass and have higher overall photosynthetic activity, a result often attributed to the root system. A particular pairing of scion and rootstock may define the root nutrient and metabolite profile (42) through absorption and shoot feedbacks.…”
Section: Discussionmentioning
confidence: 67%
“…It is also noteworthy that previous studies on fruit quality of grafted vegetables were oftentimes focused on protected production systems rather than the open-field systems used in this study. With respect to grafted tomato production in the United States, a number of studies have clearly demonstrated the great potential of using grafted plants for controlling several soil-borne pathogens and increasing plant vigor and fruit yield (Barrett et al, 2012a;King et al, 2008;Louws et al, 2010;McAvoy et al, 2012;Rivard et al, 2012); however, research is lacking as to whether the plant growth modifications as a result of grafting with vigorous rootstocks could also lead to marked changes in fruit quality properties especially with field-grown, large fruit size tomato cultivars. Therefore, it is hypothesized that grafting onto interspecific hybrid rootstocks does not adversely affect the major intrinsic quality measurements of fresh-market tomato fruit.…”
mentioning
confidence: 99%
“…Vegetable grafting has proven to be an innovative and effective technique for controlling soilborne diseases such as fusarium wilt (caused by Fusarium oxysporum), verticillium wilt (caused by Verticillium dahliae), southern blight (caused by Sclerotium rolfsii), and bacterial wilt (caused by Ralstonia solanacearum) (McAvoy et al, 2012;Rivard and Louws, 2008;Rivard et al, 2010Rivard et al, , 2012 as well as root-knot nematodes (Meloidogyne spp.) (Barrett et al, 2012;Bausher, 2009;López-Pérez et al, 2006). Grafting with certain rootstocks has also been shown to improve plant tolerance to abiotic stresses such as high salt and low temperature (Fernández-García et al, 2004;Schwarz et al, 2010).…”
mentioning
confidence: 99%